Economic Analysis of Paddy Rice Marketing in Kebbi State, Nigeria - Danmaigoro, Aliyu; Ayuba , Gona; Josiah , Simon; Ahmad , Asmau; Emmanuel Dorh, Luka (International Journal of Applied and Scientific Research, 2023)
The study analysed the economics of paddy rice marketing in Kebbi State Nigeria. A multi stage sampling technique was used. Data were collected using structured questionnaires administered to 320 paddy rice marketers. Data was analysed using Descriptive statistics, Gross margin and multiple regression analysis. Majority 79.1% had attained one form of education while 56.3% were members of cooperative with an average membership of 7 years and had an average income of about ₦70,000. Result on costs and returns of paddy rice marketing had a net return of ₦10,330 per metric tonne, the return on naira spent was 7.3% which implied that for every ₦1 spent in marketing of paddy rice, a profit of 73kobo was realised as return to investment. The factors that affect price of paddy rice shows about 62% in the total variation in price of paddy rice was greatly influenced by cooperative membership, duration of storage, marketing experience and Distance to market at 5% level of significance. The determinants of profit earned by paddy marketers shows that the variables for storage cost and transportation cost were significant at 1% while licensing was significant at 5% level of probability.